Risk factors of heart failure among patients with hypertension attending a tertiary hospital in Ibadan, Nigeria: the RISK-HHF case-control study - Oguntade, AS; Ajayi, IO (Public Library of Science, 2021)
Aim: Hypertension is the leading cause of heart failure (HF) in sub-Saharan Africa. Preventive public health approach to reduce the scourge of HF must seek to understand the risk factors of HF in at-risk populations. The aim of this study was to characterize the risk factors of HF among patients with hypertension attending a cardiology clinic.